STRATEGIES USED IN TRANSLATING IDIOMATIC EXPRESSIONS IN THE SUBTITLE OF “BEAUTY AND THE BEAST” MOVIE - Bejo Sutrisno; Nindya Puji Lestari; Budi Rachmawati (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
In translating text, translators have to be able to transfer one language into another language based on the culture, grammar and idiom in order to make the translation accurate. Hence, this research analyzed idiomatic expressions in the subtitles of Beauty and the Beast movie. It aimed to identify the types of strategies used by the translator and the meaning of idiomatic expressions found in the movie. The writer designed this research as descriptive qualitative research. In the process of analyzing the data, the researcher focuses on Baker’s idiomatic translation strategies applied by the translator to translate idiomatic expressions in the subtitles of Beauty and The Beast movie, which are similar meaning and form strategies, similar meaning but dissimilar form, translation by paraphrasing and by omission. The results of this research showed that there were 10 data of idiomatic expressions, which are 3 data used idiomatic translation by similar meaning and form, 2 data used idiomatic translation by similar meaning but dissimilar form, 3 data used idiomatic translation by paraphrase, and 2 data used idiomatic translation by omission.